Dry matter accumulation and foliar k, ca and na contents in salt-stressed cape gooseberry (physalis peruviana l.) plants (2010)
A pot experiment aimed at determining the effect of five NaClconcentrations (namely 0, 30, 60, 90 and 120 mM, determiningrespective EC values of 0.8, 3.0, 6.0, 9.0 and 12.2 dS m-1) on capegooseberry plants was set up at Humboldt University’s greenhousein Berlin, Germany. Dry weight (DW) of roots, stemsand leaves, as well as foliar content of ions K+, Ca2+ and Na+ andthe relationship they hold with one another, were determinedover a 75-day period. DW of all plant organs was observedto decrease with increasing salinity. The lowest values of thisvariable, which were recorded from the 120 mM NaCl plants,were found to be significantly smaller than those recorded at60 mM and lower salt concentrations. Salt stress effects on drymatter (DM) accumulat ion were observed to increase withplant age. Leaf K+ content increased with salinity and peakedat 90 mM NaCl, where the value was significantly higher thanthat observed at 120 mM. Foliar Ca2+ content remained unchangedat the different salt concentrations, whilst Na+ contentincreased together with salt stress. The relationship among ionconcentrations was significantly influenced only by 90 mM orhigher NaCl concentrations, which determined a progressiveincrease of the Na+/Ca2+ ratio and a similar decrease of the K+/Na+ ratio. According to the results, cape gooseberry can beconsidered as moderately tolerant to salt, as shown by the 30mM NaCl treatment, which did not affect DM accumulation inplant organs. This tolerance is also supported by steady leaf Ca2+contents at all levels of salinity, indicating that cape gooseberryuses K+ as an osmoprotectant, at least up to 90 mM NaCl.